2021
DOI: 10.3390/pathogens10050587
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Pathogens in Ticks Collected from Wild Ungulates in North-Eastern Poland

Abstract: This study was carried out in north-eastern Poland during two hunting seasons between 2018 and 2020. Ticks (Ixodes ricinus and Dermacentor reticulatus) were removed from wild cervids and boars and examined for the presence of Borrelia spirochetes and Rickettsiales members: Rickettsia spp. and Anaplasma phagocytophilum. The present study contributes to the knowledge of even-toed ungulates, which are an important reservoir of the above-mentioned pathogens and a potential source of infections for humans through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 61 publications
1
13
1
Order By: Relevance
“…The results of the DNA sequencing of the gltA gene suggested that D. reticulatus was infected mainly with R. raoultii and I. ricinus with R. helvetica . The rate of infection in D. reticulatus was slightly lower than that revealed in ticks feeding on wild ungulates (49%) in north-eastern Poland [ 28 ] and also in the population of questing D. reticulatus of other regions of Poland (40.7–44%) [ 10 , 30 , 37 , 38 , 39 ]. In European countries, the percentage of infected D. reticulatus with Rickettsia spp.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results of the DNA sequencing of the gltA gene suggested that D. reticulatus was infected mainly with R. raoultii and I. ricinus with R. helvetica . The rate of infection in D. reticulatus was slightly lower than that revealed in ticks feeding on wild ungulates (49%) in north-eastern Poland [ 28 ] and also in the population of questing D. reticulatus of other regions of Poland (40.7–44%) [ 10 , 30 , 37 , 38 , 39 ]. In European countries, the percentage of infected D. reticulatus with Rickettsia spp.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, spirochaetes from the B. burgdorferi complex were detected only in I. ricinus . Although the specific DNA of that bacteria has been detected in D. reticulatus in other regions of Poland [ 10 , 28 , 29 , 30 ] their role as a vector was not confirmed. Among the examined I. ricinus ticks, 20% of them were infected with Borrelia , with the predominance of pathogenic B. afzelii (52.4%) and B. garinii (42.1%).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, nucleotide sequence analysis revealed that only R. helvetica was present in the examined tick populations from four sites in Western Pomerania. The latest research by Kowalec et al [ 29 ] and Michalski et al [ 30 ] conducted in I. ricinus ticks collected from central and northeastern Poland showed the presence of the species R. raoulti and the novel “ Candidatus Rickettsia mendelii ” in these ticks, apart from R. helvetica and R. monacensis . The authors’ current research, unpublished (material harvested in 2019–2020), in ticks collected from urbanized areas of Western Pomerania has not yet revealed the presence of species other than R. helvetica and R. monacensis.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the relative homogeneity of the area in terms of the shape of the surface and natural features and the mosaic structure with complexes of forests, lakes, peat bogs, used meadows, pastures, agricultural land, and relatively low human interference [ 62 ]. This ensures the optimal structure of vegetation and microclimate for ticks at the studied sites and access to mammalian hosts (rodents, deer) [ 63 , 64 ], which affects the reproduction of ticks and the maintenance of their population.…”
Section: Discussionmentioning
confidence: 99%